Autograph letter signed by William Wallace - Wallace, William, 1860-1940:::Creator::::::::::::; Fricker, Herbert A., 1868-1943:::Contributor:::::::::::: (London; United Kingdom, 2021)
Autograph letter signed by William Wallace, London, dated Feb. 2, 1913, possibly to the choral conductor Herbert A. Fricker, that in a postscript mentions a performance of Beethoven's Ninth Symphony scheduled for March 13, 1913.